Zadig, or, The book of fate - Voltaire, 1694-1778. ([Waiheke Island] : Floating Press, 2009)
Enlightenment philosopher Voltaire's novel.
eBooks on EBSCOhost
Keywords: Philosophers -- Iraq -- Babylon (Extinct city) -- Fiction; Philosophes -- Irak -- Babylone (Ville ancienne) -- Romans, nouvelles, etc; Philosophers; Iraq -- Babylon (Extinct city); Fiction